A simulation-based approach to assessing the relationship between mutual fund size and performance - Molyneux, Matthew (Department of Finance and Tax, 2021)
This study examines how mutual fund size affects performance. Academic literature on this topic is extensive but has yielded conflicting results. Some studies find a distinct relationship between fund size and risk-adjusted returns while others do not; some studies also posit that an optimal fund size exists where risk-adjusted returns are maximised. The size of equity mutual funds in South Africa and the market dynamics of the Johannesburg Stock Exchange provide an interesting context within which to analyse the relationship between size and performance. In this study, hypothetical portfolios are created, and an allocation procedure is used to distribute capital to these hypothetical portfolios. The allocation procedure distributes capital to the portfolio stocks by controlling for each stock's yearly volume traded. This method works to distribute capital up until a certain fund size; beyond that size, the hypothetical portfolio might no longer be fully invested in the random portfolio. To control for this, the simulation model engages in a routine to discard the stock with the lowest volume-traded level from the portfolio and reselect another stock from the investable universe with a higher volume-traded level. This process is repeated until the portfolio is fully invested. Stock selection and investment dates are randomised and variance reduction techniques are used to improve the efficiency of the simulation, and 10 000 simulation runs are performed. The results of the simulation found a non-monotonic relationship between mutual fund size and performance over a one-year holding period, consistent with some research internationally and in South Africa. Over a two- and three-year holding period, mutual fund size and returns, however, seem to be negatively correlated. Over the three holding periods, the study suggests that the optimal equity mutual fund size in South Africa is approximately ZAR 2bn. Portfolios with assets under management greater than ZAR 2bn see their returns decrease noticeably as fund size continues to increase. These findings are supported by comparing simulated returns to actual benchmark returns over the same random periods. The results of this study suggest that mutual funds should be aware that consistent increases in assets under management could negatively affect performance and that all funds should ensure that total assets under management do not exceed ZAR 2bn.